Technology acceptance of Pharmacy Information System (PIS) among pharmacy workers in public health facilities under health department of federal territory of Kuala Lumpur and Putrajaya / Abdul Hafeez Ahmad Hamdi - Ahmad Hamdi, Abdul Hafeez (2017)
Introduction: Pharmacy Information System(PIS) has the potential to improve organizational performance. Ministry of Health (MOH) has taken strategic initiatives to transform pharmacy in public health sector towards a more efficient and effective health system using a single standardize system. Regardless of the potential benefits of the system, the success and effectiveness of implemented PIS cannot be fully realized if such application has a poor technology acceptance among pharmacy workers. This study was aimed to identify the determinants which influence the technology acceptance of PIS among pharmacy workers using Unified Theory of Acceptance and Use of Technology (UTAUT). Methodology: This study was a cross-sectional, multicenter, online web survey that was conducted among PIS users (pharmacists and pharmacist assistants) who worked in hospitals, public health clinics, and health district offices under the Health Department of Federal Territory Kuala Lumpur And Putrajaya. Structural Equation Modelling (SEM) with AMOS Ver 23 was used to identify the determinants of pharmacy workers behavior intention to use the PIS. Result: A total of 105 returned questionnaires which represented a response rate of 82.6%. Descriptive statistics in this study suggested that pharmacy workers have a positive perception towards PIS. The results of the measurement model showed that the model in this study has achieved unidimensionality, goodness-of-fit, construct reliability, and validity. The model in this study provided a powerful explanation of the behavior intentions among pharmacy workers to use PIS (R2 : 0.73). The results of structural equation modeling showed that performance expectancy (β:0.26, p<0.05), effort expectancy (β:0.34 p<0.05), social influence (β:0.25, p<0.05), and facilitating conditions (β:0.23 p<0.05) were all significant determinants of behaviour intention to use PIS. Conclusion: The UTAUT model is useful in explaining pharmacy workers behavior intention to use PIS. Pharmacy workers who believed the system to be easy to use, increase their job performance, supported by their colleague and top management, the existence of sufficient resources and knowledge are more likely to accept the system. Health organization management should continue developing programs that support pharmacy workers performance expectancy, effort expectancy, facilitating conditions and social influence to ensure successful implementation and sustainability of recently implemented PIS in the public sector.